Evaluating the therapeutic impact of Compound Polymyxin B Ointment on postoperative wound healing in patients with perianal abscesses - Yan-Zhu Li; Fu-Rong Zhou; Xiao-Juan Chen; Yong-Gan Liu (Frontiers in Medicine)
IntroductionPerianal abscesses pose a considerable obstacle in the realm of postoperative wound treatment owing to their elevated susceptibility to infection and associated consequences. Polymyxin B Ointment, a compound renowned for its antibacterial qualities, has the potential to provide therapeutic advantages by promoting wound healing and mitigating postoperative problems.MethodsOur institution conducted a thorough retrospective analysis spanning from December 2020 to December 2023 to assess the effectiveness of Compound Polymyxin B Ointment in the management of surgical wounds in patients diagnosed with perianal abscesses. The research encompassed a cohort of 100 individuals, who were classified into two groups: a control group that received conventional postoperative care, and an observation group that received supplementary treatment with Compound Polymyxin B Ointment. The evaluation of clinical outcomes involved measuring wound healing effectiveness, pain intensity using the Visual Analogue Scale (VAS), tissue swelling, exudation, necrotic tissue shedding time, duration of hospital stays, and rate of reduction in wound area.ResultsThe group that received Compound Polymyxin B Ointment had significant enhancements in wound healing, as seen by a noteworthy 46% of participants completing complete healing, in contrast to the control group’s 32%. The VAS was used to quantify pain levels, and the observation group reported a substantial reduction of almost 50% in ratings. Furthermore, this cohort exhibited a 45% decrease in edema and a 50% decline in exudation rates, in addition to a 50% acceleration in the shedding of necrotic tissue. The duration of the hospital stay was reduced by 40%, and the reduction in wound area was 18% higher, suggesting a more effective healing process. In addition, it is worth noting that the observation group had a lower incidence of problems, so underscoring the effectiveness of the ointment in facilitating wound healing and mitigating postoperative difficulties.DiscussionThe utilization of Compound Polymyxin B Ointment as an adjuvant measure in the surgical treatment of perianal abscesses has been found to have a substantial positive impact on wound healing, pain relief, and complication reduction. This finding provides evidence for the possibility of the ointment as a helpful inclusion in post-surgical wound care procedures among this specific group of patients.